Ciguatoxins: Cyclic Polyether Modulators of Voltage-gated Iion Channel Function - Richard J. Lewis; Graham M. Nicholson (Marine Drugs, 2006)
Ciguatoxins are cyclic polyether toxins, derived from marine dinoflagellates, which are responsible for the symptoms of ciguatera poisoning. Ingestion of tropical and subtropical fin fish contaminated by ciguatoxins results in an illness characterised by neurological, cardiovascular and gastrointestinal disorders. The pharmacology of ciguatoxins is characterised by their ability to cause persistent activation of voltage-gated sodium channels, to increase neuronal excitability and neurotransmitter release, to impair synaptic vesicle recycling, and to cause cell swelling. It is these effects, in combination with an action to block voltage-gated potassium channels at high doses, which are believed to underlie the complex of symptoms associated with ciguatera. This review examines the sources, structures and pharmacology of ciguatoxins. In particular, attention is placed on their cellular modes of actions to modulate voltage-gated ion channels and other Na+-dependent mechanisms in numerous cell types and to current approaches for detection and treatment of ciguatera.